2022
DOI: 10.1021/acsami.1c23213
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Palladium Nanoparticles with Surface Engineered Metal–Organic Frameworks for Cell-Selective Bioorthogonal Catalysis and Protein Activity Regulation

Abstract: Bioorthogonal catalysis provides a powerful tool to perform non-natural chemical reactions in living systems to dissect complex intracellular processes. Its potency to precisely regulate cellular function, however, is limited by the lack of bioorthogonal catalysts with cell selectivity. Herein, we report that palladium nanoparticles deposited on metal−

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Furthermore, the cellular study revealed the MAPK/ERK signaling of cancer cells could be controlled via AS1411@Pd@UiO-66-mediated bioorthogonal activation of Proc-4-OHT, which was viewed as a promising approach to manipulate cell fate and treat cancer. 32 Collectively, MOFs provide lots of convenience and advantages for developing versatile TMC-based bioorthogonal nanozymes. Thus, it is also worthwhile to proceed with the exploration.…”
Section: The Development Of Tmc-based Bioorthogonal Nanozymesmentioning
confidence: 99%
“…Furthermore, the cellular study revealed the MAPK/ERK signaling of cancer cells could be controlled via AS1411@Pd@UiO-66-mediated bioorthogonal activation of Proc-4-OHT, which was viewed as a promising approach to manipulate cell fate and treat cancer. 32 Collectively, MOFs provide lots of convenience and advantages for developing versatile TMC-based bioorthogonal nanozymes. Thus, it is also worthwhile to proceed with the exploration.…”
Section: The Development Of Tmc-based Bioorthogonal Nanozymesmentioning
confidence: 99%
“…[ 109 ] The Wang group coated Pd@UiO‐66 MOF with AS1411 DNA aptamers through coordination between zirconium and the DNA phosphate backbone (AS1411@Pd@UiO‐66) ( Figure a). [ 110 ] To confirm cancer selectivity, the authors incubated three cancer cell lines (HCT‐116 colon cancer cells, SiHa cervical cancer cells, and HeLa) and two non‐cancer cell lines (HK‐2 derived from human kidney proximal tubule epithelial cells and HEK‐293T derived from human embryonic kidney cells grown in tissue culture) with the targeting MOF nanozyme (0.1 g L −1 ) and activated a rhodamine‐based pro‐dye through Pd‐mediated uncaging reactions (Figure 11a). Flow cytometry analysis revealed that pro‐rhodamine was bioorthogonally activated in 70–80% of cancer cells and 25–45% of non‐cancer cells, demonstrating the effectiveness of MOF nanozyme in targeting cancer cells.…”
Section: Step 4: Engineer Nanozyme Surfaces For Localization and Targ...mentioning
confidence: 99%
“…Pd-based TMCs have been encapsulated into various nanomaterials, including polymer, Au, and silica NPs, MOFs, and enzyme cages, to improve their biocompatibility and catalytic performance [ 191 194 , 196 , 215 217 ]. For example, Wang et al deposited Pd(0) NPs on a zirconium oxide MOF and decorated the surface with a DNA aptamer (AS1411) that targets nucleolin-overexpressing cancer cells (Fig.…”
Section: Bioorthogonal Nanozymes (Bonzs)mentioning
confidence: 99%